Effects of irradiation conditions on the radiation sensitivity of microorganisms in the presence of OH-radical scavengers. (2nd December 2018) - Múčka, Viliam; Červenák, Jaroslav; Reimitz, Dan; Čuba, Václav; Bláha, Pavel; Neužilová, Barbora
Abstract: Purpose: The purpose of the paper was to investigate the protective effect of some scavengers of OH radicals (hydroxyl radicals) on the radiation sensitivity of bacteria (in some cases also yeast) under normoxic (in air) or hypoxic (suboxic) conditions and to compare the obtained results with those published earlier for the yeast, all in a wide interval of irradiation conditions. Another aim was to investigate a possible impact of the reaction order of the reaction between the scavengers and the OH radicals on the protection of the cells. Materials and Methods: In order to study the protective effect of OH scavengers we used various concentrations of methanol and potassium formate (in some cases also ethanol) in isotonic salt solutions. These solutions containing living bacteria ( Escherichia coli ) or yeast ( Saccharomyces cerevisiae ) were irradiated with 60 Co radiation using various doses and dose rates. Irradiation was performed in air, in some cases under the hypoxic conditions. The number of surviving cells was determined prior to and after irradiation in suspension with and without scavengers. The surviving fractions after irradiation with and without scavenger were evaluated. Results: The surviving fraction of bacterial cells increases linearly with increasing concentration of both scavengers. The fraction of surviving cells does not increase with increasing concentration of the scavengers under suboxic conditions. The protective effect Ϭ increases linearly with increasing scavenging efficiency and this dependence is much sharper under normoxic conditions than under suboxic ones. The specific protection k is much higher for the methanol than for the potassium formate. Conclusions: The basic characteristics of the impact of scavengers of OH radicals on radiation sensitivity of both bacteria and yeast are the same in a wide interval of doses and dose rates. The specific protection effect is much higher under the normoxic conditions. This protective effect is inversely proportional to the rate constant of the reaction between the scavenger and the OH radicals. It seems to be obvious that the presence of oxygen during irradiation is a necessary condition for the protective action of the scavengers which may be partially controlled by some transport processes and may be connected with the radiation sensitivity of the cells. On the other hand, the change of the reaction order of the reaction of the scavenger with the OH radicals has turned out to be unimportant.